2023
DOI: 10.3390/medicina59061104
|View full text |Cite
|
Sign up to set email alerts
|

High Fat Diet Exaggerate Metabolic and Reproductive PCOS Features by Promoting Oxidative Stress: An Improved EV Model in Rats

Abstract: Background and Objectives: Polycystic ovary syndrome (PCOS) is a frequent multifactorial endocrinopathy affecting women in the reproductive period, often associated with infertility and metabolic disorders. The use of animal models helps to better understand etiopathogenesis, enabling the examination of the effects of certain drugs in order to discover the best possible therapeutic approach. We tried to investigate the additional effect of estradiol-valerate (EV) and high-fat diet (HFD) in female rats to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
(102 reference statements)
1
2
0
Order By: Relevance
“…On the other hand, our study confirmed that obesity and oxidative stress are closely linked; this was demonstrated by an increased lipid peroxidation, decreased antioxidant enzyme activities, such as SOD, CAT, and GPx, as well as depletions in non-enzymatic antioxidants such as the -SH group and GSH. These data align with previous reports indicating that liver steatosis is associated with adipose tissue ROS production [17,73,74]. Indeed, the mechanisms underlying non-alcoholic fatty liver disease (NAFLD) are induced by a perturbation in the mitochondrial metabolism, leading to the overproduction of ROS in the liver [73].…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, our study confirmed that obesity and oxidative stress are closely linked; this was demonstrated by an increased lipid peroxidation, decreased antioxidant enzyme activities, such as SOD, CAT, and GPx, as well as depletions in non-enzymatic antioxidants such as the -SH group and GSH. These data align with previous reports indicating that liver steatosis is associated with adipose tissue ROS production [17,73,74]. Indeed, the mechanisms underlying non-alcoholic fatty liver disease (NAFLD) are induced by a perturbation in the mitochondrial metabolism, leading to the overproduction of ROS in the liver [73].…”
Section: Discussionsupporting
confidence: 91%
“…EVs have been found to stimulate cell proliferation, angiogenesis, protein expression, molecular transport, and apoptosis [33,34,37,43,50,51]. EVs are also implicated in various pathological conditions like cancer, metabolic disorders, and inflammatory lung diseases, transmitting information between stromal, immune, and dysfunctional cells, thereby influencing pathogenesis and outcomes [52][53][54]. They are also associated with a wide range of other pathologies, including cardiovascular, renal, and musculoskeletal diseases [55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…Under the influence of insulin, the ratio of follicle-stimulating hormone (FSH) and LH changes, and the level of LH increases significantly. LH hypersecretion stimulates the cells to produce androgens and reduces the effect of FSH [9].…”
Section: Introductionmentioning
confidence: 99%